2022
DOI: 10.1016/j.jaad.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic correlation of cutaneous COVID-19 vaccine reactions including V-REPP: A registry-based study

Abstract: Background: Cutaneous reactions after COVID-19 vaccination have been commonly reported; however, histopathologic features and clinical correlations have not been well characterized. Methods:We evaluated for a history of skin biopsy all reports of reactions associated with COVID-19 vaccination identified in an international registry. When histopathology reports were available, we categorized them by reaction patterns.Results: Of 803 vaccine reactions reported, 58 (7%) cases had biopsy reports available for revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
181
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(203 citation statements)
references
References 27 publications
8
181
0
14
Order By: Relevance
“…The European Medicines Agency (EMA) has authorized four vaccines in Europe: Pfizer-BioNTech/Cominarty, Moderna/Spikevax, AstraZeneca/Vaxzevria and Johnson&Johnson /COVID-19 vaccine Janssen. The first three are given in two doses some weeks apart, whereas Janseen vaccine is administered as single dose [3] , [4] , [5] .…”
Section: Resultsmentioning
confidence: 99%
“…The European Medicines Agency (EMA) has authorized four vaccines in Europe: Pfizer-BioNTech/Cominarty, Moderna/Spikevax, AstraZeneca/Vaxzevria and Johnson&Johnson /COVID-19 vaccine Janssen. The first three are given in two doses some weeks apart, whereas Janseen vaccine is administered as single dose [3] , [4] , [5] .…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2-vaccine-associated cutaneous eruptions encompass a growing spectrum of clinicopathological varieties, including local injection site reactions, urticarial eruptions, morbilliform eruptions, pernio/chilblain-like lesions, cosmetic filler reactions, herpes zoster and herpes simplex flares, pityriasis rosea-like eruptions (11,20,21). Autoimmune bullous skin diseases have also been observed following SARS-CoV-2-vaccination, with approximately 34 individual cases of vaccine-associated BP currently described (12,14,17,(22)(23)(24)(25)(26)(27)(28) (Supplementary Table 1). According to the registry-based studies by McMahon et al, BP-like eruptions accounted for 20% (12/58) of biopsy-proven SARS-CoV-2-vaccine-associated cutaneous reactions and 1.5% overall (11,22).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first cases associated with the Moderna vaccine. McMahon et al [9] performed a registry-based study where they discussed the occurrence of vaccine-related eruption of papules and plaques (V-REPP) after COVID-19 vaccination. Among these skin manifestations, lichen planus was reported in four cases, three of which were related to the Pfizer vaccine and one to the Moderna vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The physiopathological mechanisms underlying the relationship between LP and vaccination for COVID-19 are still poorly understood, however, it has been shown that after such vaccines there can be a stimulation of the immune response of T helper lymphocytes type 1 (Th1) [10], leading to the stimulation of the production of interleukin (IL)-12, tumor necrosis factor (TNF)a, and interferon (IFN)c, cytokines involved in the pathogenesis of LP [11]. What emerges from the literature at present, is that COVID-19 vaccines can cause strong T-cell responses [9][10][11]. The mechanism by which they might elicit immunostimulatory effects, including triggering T-cell-dependent disorders, requires further study.…”
Section: Discussionmentioning
confidence: 99%